Analytical Treatment of Parametric Effects in a Ring Resonator - I.N. Nawi; H. Hairi; S. Daud; M.S. Aziz; J. Ali; P.P. Yupapin (My University, 2011)
We propose two systems of a nano-waveguide to study the effects of ring resonator radii and coupling coefficient. The first proposed system is introduced as a single ring resonator. The change of the center wavelength from the output signal is monitored and analyzed. It shifts towards higher wavelength of the spectrum. The multistage ring resonator system consists of two micro and a nano ring resonators that can be integrated into a single system. The soliton pulse propagating within a Kerr type nonlinear medium is used to generate the large bandwidth signals. By using the suitable parameters, for instance, the input power of soliton, coupling coefficients, and ring radii, the short-wave and millimetre-wave output signals can simultaneously be generated in a multi-stage ring resonator (MMRR). We found that by using the MMRR, a desired response can be achieved over a broader portion of the spectrum compared to the single-stage ring resonator (SMRR) in which it is more preferable in applications.
Keywords: Optical ring resonators; Split-ring resonator; Photonic and Optical Devices